Resíduos da construção civil aliados à P+L - Kunkel, Neidi (2009)
This work discourses about the construction residues and demolition generated by the building site section. The work of the emphasis in the importance of the reaproveitament of the same, because the accumulation of these materials besides causing environmental problems represents an increment in the cost of the work. Presents the weak points of the process and opportunities of improvements, as well as search to give some back-up with relationship to the normative and economical aspects related to the waste. Finally, suggests roads they be her followed for the companies of the section, seeking the improvement of your process and ecological maturity. The objective of this work is to show the variables that are related to the residues, presenting the problems and showing some solutions to avoid the generation of residues in the building site, through a program of Cleaner Production. The adopted methodology was the collection of information and the theoretical and practical knowledge related to the subject.